Development of the Bestari Green Waste Bank: Integration of Creative Economy and Green Economy in Serang City - Julia Safitri; Fitri Normasari; Is Eka Herawati; Ratih Purnamasari; Putri Yudha Septiana; Jaka Pamungkas (MOVE: Journal of Community Service and Engagement, 2026)
This study analyzes the development strategy of the Bestari Green Waste Bank in Serang City through the integration of the creative economy as the main driver of the transition to a green economy. Facing the urban waste management crisis, a paradigm shift is needed from the linear "take-use-dispose" model to a circular model that adds value to waste materials. Using descriptive qualitative methods, this study evaluates the operational mechanisms and socio-economic impacts of the waste bank program through field observations and document studies. The research findings indicate that the application of creativity elements in inorganic waste processing can transform waste commodities that were initially low in value into craft products with high economic value. This upcycling process significantly contributes to reducing the volume of residue sent to the final processing site, while creating income diversification for the local community. Theoretically, this integration proves that the synergy between human creativity and environmental governance is key to achieving green economic sustainability at the grassroots level. The implications of this research suggest the importance of strengthening design capacity and synchronizing local government policies to expand the scale of the economic and ecological impacts of this model.